Fires of Motivation: A Journey through Influencing factors- A narrative Review. - Siti Fatimah Sa’at; Nur Ain Mahat; Mazlinda Musa; Rohani Mamat; Zulkhairul Naim Sidek Ahmad; Mohamad Firdaus Mohamad Ismail (Jurnal Al- Sirat, 2023)
Introduction: Employee motivation is a critical aspect of organizational success, characterized by an employee's passion, energy levels, dedication, and innovative contributions on a daily basis. Rooted in the Latin word "movere," which signifies "moving," motivation is recognized as a behavior that must be directed towards achieving specific goals and outcomes. Employee motivation revolves around an employee's sense of engagement and empowerment within the organization's objectives. Objective: This research aims to explore the multifaceted nature of employee motivation, specifically investigating the interplay between intrinsic and extrinsic motivation and the internal and external factors that influence it. Through the analysis of ten pertinent articles, this study seeks to identify key determinants that enhance working motivation across diverse fields. Method: The research involved a comprehensive review and analysis of ten selected articles that delved into the intricacies of employee motivation. These articles were chosen to provide a comprehensive understanding of the subject, encompassing both intrinsic and extrinsic motivational factors, as well as internal and external determinants. Thematic analysis was employed to extract and categorize relevant data. Results: The findings of this study shed light on the pivotal role of both internal and external factors in shaping an individual's working motivation. Internally, factors such as fatigue, personal interests, and self-attitude emerge as significant influencers of motivation levels. Externally, factors like leadership style, the work environment, and human dynamics were identified as potent drivers of working motivation. These results underscore the intricate interplay between an employee's internal disposition and the external context in which they operate, emphasizing the need for a holistic approach to motivation within organizations. Conclusion: This research emphasizes the need to consider various factors that affect employee motivation. Intrinsic and extrinsic motivation are not enough. Internal and external elements also matter. Organizations must act on these findings to boost productivity and success.